2016
DOI: 10.1159/000442585
|View full text |Cite
|
Sign up to set email alerts
|

Elevated C-Reactive Protein Is Associated with Cognitive Decline in Outpatients of a General Hospital: The Project in Sado for Total Health (PROST)

Abstract: Background/Aims: We aimed to determine whether the concentration of serum C-reactive protein (CRP) is associated with cognitive function in an adult Japanese population. Methods: Participants of this cross-sectional study were from a subgroup of the Project in Sado for Total Health (PROST; n = 454; mean age, 70.5 years). The cognitive state was evaluated using the Mini-Mental State Examination (MMSE), and those with an MMSE score <24 were considered ‘cognitively declined'. Concentrations of serum high-sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 64 publications
5
31
2
Order By: Relevance
“…Our findings correlate with other similar studies (21). Level of CRP in our study did not correlate significantly with global cognitive function unlike previous findings (22)(23)(24)(25). Our study showed that elevated PTH levels and severity of secondary hyperparathyroidism statistically significantly correlates with space and time orientation disorders.…”
Section: Discussionsupporting
confidence: 80%
“…Our findings correlate with other similar studies (21). Level of CRP in our study did not correlate significantly with global cognitive function unlike previous findings (22)(23)(24)(25). Our study showed that elevated PTH levels and severity of secondary hyperparathyroidism statistically significantly correlates with space and time orientation disorders.…”
Section: Discussionsupporting
confidence: 80%
“…Several reports support this hypothesis regarding the relationship between inflammation and cognitive function. 17 Furthermore, high-sensitivity CRP has been shown to be a useful biomarker for cognitive impairment, [18][19][20] vascular dementia 21 and AD 22,23 in population-based studies. Inflammation is also known to be associated with risk factors for dementia, such as aging processes, tumor necrosis factor-α and tau proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Because inflammation also has been shown to be associated with increased risk for adverse CVD events(32, 33) and impaired cognitive function, (34) we also sought to determine whether the relation between lifestyle factors and neurocognitive function is explained by C-reactive protein and CVD risk factors.…”
Section: Introductionmentioning
confidence: 99%